BTG2 and SerpinB5, a novel gene pair to evaluate the prognosis of lung adenocarcinoma - Yang, Wanting; Wei, Chunli; Cheng, Jingliang; Ding, Ran; Li, Yan; Wang, Yonghua; Yang, Yinfeng; Wang, Jinghui (Frontiers in Immunology, 2023)
Due to the limitations of clinical research, it was often found in the late stage of Lung adenocarcinoma, finding suitable prognostic markers has become an important challenge. BTG2 and SerpinB5 play important roles in tumor. The BTG2 and SerpinB5 were studied as a gene pair for the first time. Our aim is to explore the gene expression of BTG2 and SerpinB5 in LUAD and whether they can be used as potential prognostic markers, and to build a prognostic model to evaluate the survival rate of patients. First, by studying the changes of gene expression level, we found that compared with normal lung tissue, BTG2 gene expression was down-regulated and SerpinB5 was up-regulated in LUAD. Moreover, the prognosis of low expression of BTG2 was poor, and that of high expression of SerpinB5 was poor which was calculated by Kaplan–Meier survival analysis. At the same time, both of them can be used as independent prognostic factors by Cox regression analyses. In addition, the prognosis models of the two genes were constructed respectively in this study, and their prediction effect was verified by external data. Besides, the relationship between this gene pair and the immune microenvironment was explored, both of them are related to immune microenvironment and immunotherapeutic response by ESTIMATE algorithm. Combining the above results, when patients have low expression of BTG2 and high expression of SerpinB5, the prognosis of LUAD patients was poor, which will be accompanied by the increase of macrophages, which may be a reason for the poor prognosis of LUAD. The immunophenoscore (IPS) was used to evaluate the response to immune checkpoint inhibitors therapy. Patients with high expression of BTG2 and low expression of SerpinB5 have higher immunophenoscore for CTLA-4 and PD-1 inhibitors than patients with low expression of BTG2 and high expression of SerpinB5, which indicates that such patients have more obvious effect of immunotherapy. These results collectively demonstrated that BTG2 and SerpinB5 might serve as a potential prognostic biomarker and novel therapeutic target for LUAD. Thus, further research is needed to validate our findings and promote the clinical application.